PECTIN EXTRACTION OF SIAMESE PUMPKIN SKIN WITH CONCENTRATION OF HYDROCHLORIC ACID (HCL) SOLUTION - Priyantono, Eko; tomi, tomi (Universitas Tadulako, 2024)
Pectin is commonly used to soften jellies, jams and other products. In addition, fruits and vegetables contain pectin to maintain plant cells. Pectin is a high-value food fiber that can be called a functional food. This pectin plays an important role in gel formation and as a stabilizer in the manufacture of jelly, jam, and marmalade. Pectin is widely used in the food industry because it has the ability to act as a fruit preservative and to form a gel as a base for forming jelly as well as a thickener and stabilizer, while in the food industry it is used in the production of jams, confectionery, pasta and dairy products. The objectives of this study are: To determine the physical and chemical properties and quality of pectin extracted with hydrochloric acid (HCL) and to achieve the optimal concentration of hydrochloric acid solvent. The study was conducted in the agroindustrial laboratory of the agricultural faculty of the university of Tadulako, Palu, Sulawesi Tengah. The duration of the study will be from october 2022 to january 2023. This study is an experimental study based on fruit skins with hydrochloric acid concentrations using a complete one-factor random design (RAL) pattern. The factors tested consist of several hydrochloric acid concentration levels, namely: 1N; 1.5N; 2N; 2.5N; AND 3N. The analytical parameters observed include: yield, methoxil level, water level, ash level and galacturonal acid level. the results of the research carried out that: the concentration of HCl solvent in the extraction of pectin fruit peels is best at a concentration of 3N. The concentration of 3N HCl extracted from the Siamese Pumpkin Skin physical characteristics, namely yield 36.11%, while the chemical properties were 1.99% water content, 0.42% ash content, 3.615% methoxyl content and galactoronate acid 137.88%. and for provide the best quality of pectin from fruit siamese pumpkin skin according to the quality standards set by ippa (international pectin manufacturers association), so it has potential as a thicker and gel forming. based on the results of the research conclusion: Concentration of hydrochloric acid solvent, on extract siamese pumpkin skin best at 3N concentration.